Debinding study of injection molded CoCrMo alloy powder using palm based binder system - Noorsyakirah, Abdulah; Shamsul Baharin, Jamaludin, Prof. Dr.; Mohd Afian, Omar (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.